We Were There: Individual, Social, and Cultural Memory in Punk Memoirs by Women - Cristina Garrigós (European Journal of Life Writing)
This article analyzes how three of the different types of memory proposed by Aleida Assmann (individual, social, and cultural) are intertwined in the memoirs written by female punk musicians. In these works, there is a strong emphasis on the fact that the narrative persona belongs to a social group, thereby inscribing herself in the culture of the times. The individual memories of the authors, and the shared experiences of the generation to which they belong, thus become a part of the creation of the cultural memory of punk. This article seeks to provide new knowledge of the participation of women in punk via the study of the representation of memory in three memoirs: Alice Bag’s Violence Girl: East L.A. Rage to Hollywood Stage. A Chicana Punk Story (2011), Viv Albertine’s Clothes, Clothes, Clothes, Music, Music, Music, Boys, Boys, Boys (2014), and Chrissie Hynde’s Reckless: My Life as a Pretender (2016). These memoirs demonstrate that the authors contribute to writing the history of punk by inscribing themselves into it. Aware that the presence of women has not previously been sufficiently acknowledged, they do so by interweaving their individual memories with social ones, in order to attest to the birth of punk as culture.